Hyperglycemia-induced accumulation of advanced glycosylation end products in fibroblast-like synoviocytes promotes knee osteoarthritis - Qingxian Li; Yinxian Wen; Linlong Wang; Biao Chen; Jun Chen; Hui Wang; Liaobin Chen (2021)
Abstract Osteoarthritis (OA) is significantly associated with diabetes, but how hyperglycemia induces or aggravates OA has not been shown. The synovium plays a critical role in cartilage metabolism and substance exchange. Herein, we intended to investigate whether and how hyperglycemia affects the occurrence and progression of OA by influencing the synovium. In patients with knee OA and diabetes (DM OA), we found a more severe inflammatory response, higher endoplasmic reticulum stress (ERS) levels, and more advanced glycosylation end products (AGEs) accumulation in the synovium than in patients without diabetes. Subsequently, we found similar results in the DM OA group in a rat model. In the in vitro cocultivation system, high glucose-stimulated AGEs accumulation, ERS, and inflammation in rat fibroblast-like synoviocytes (FLSs), which resulted in chondrocyte degeneration due to inflammatory factors from FLSs. Furthermore, in the synovium of the DM OA group and FLSs treated with high glucose, the expression of glucose transporter 1 (GLUT1) and its regulatory factor hypoxia-inducible factor (HIF)-1α was increased significantly. Inhibitors of HIF-1α, GLUT1 or AGEs receptors attenuated the effect of high glucose on chondrocyte degradation in the FLS-chondrocyte coculture system. In summary, we demonstrated that hyperglycemia caused AGEs accumulation in FLSs via the HIF-1α-GLUT1 pathway, which increases the release of inflammatory factors from FLSs, subsequently inducing chondrocyte degradation and promoting OA progression.